(Experimenting with) Living Architecture: a practice perspective. Issue 1 (20th July 2016) - Flynn, Emma
Abstract : Energy from depleting fossil fuels consumed in the construction and operation of buildings accounts for approximately half of the UK's emissions of carbon dioxide. With global warming increasing, amplifying extreme weather conditions and frequency, buildings can no longer remain static and unresponsive to their surrounding environment. Architecture must become adaptive, reactive to changes in climate, and reducing CO2, not generating it. As a tree responds to and moderates its surrounding environment, nature can become a key inspiration in developing mechanisms to reduce the impact of climate change and resource depletion. At Astudio, our research looks to incorporate fundamental processes in living and natural systems in the architectural design of responsive surfaces and building services. A form of synthetic biology, these 'bio-responsive' designs combine both biological and technical systems, which adapt to, and harvest from, the immediate climatic environment. This paper will demonstrate the potential of synthetic biology in improving the resilience of our built environment, documented through our practice research and our collaborations with industry and academic institutions to date. Astudio are world-class architects focused on reducing our buildings' impact on the environment. Our courage in the pursuit new ways to reduce carbon and change behaviors gained us the coveted title of Architectural Practice of the Year in 2012. This unprecedented achievement led us to establish our research and development group, whose role is to investigate new ways of seeing and thinking about the challenges we face in the industry. With this group, we explore visionary concepts that enable us to consider how we may cross boundaries taking us out of architecture and work with different fields of expertise that can help us solve sustainable construction in new ways. We look to the future to propose buildable solutions today.